Children's reading comprehension and oral reading fluency in easy text - Spear-Swerling, Louise (Reading and Writing, 2006)
This study explored third-graders' oral reading fluency (ORF) in easy text in relation to their third- and fourth-grade reading comprehension. It also examined the children's performance on two different measures of text exposure, a self-report questionnaire and a title-recognition test. Although third-graders' ORF related significantly to their reading comprehension, oral language comprehension accounted for most of the variance in reading comprehension, whereas single word reading speed accounted for most of the variance in ORE Third-grade reading comprehension and ORF each predicted unique variance in children's scores on a fourth-grade state-mandated reading comprehension assessment. Scores on the self-report questionnaire correlated significantly with third-grade ORF and fourth-grade reading; the self-report accounted for reliable variance in ORF even with all of the other reading ability variables entered first. Results are consistent with the viewpoint that text exposure affects reading fluency. They also demonstrate that ORF is a valuable predictor of middle-elementary children's reading comprehension, even when the ORF measure employs very easy text in which children achieve near-perfect word accuracy.
40 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/050-531-179-017-917 tex.type: [object Object]
Keywords: Comprehension; Fluency; Reading; Text exposure; dept.sed; peer-reviewed